Economic links from bonds and cross-stock return predictability - Feng, Jian; Huo, Xiaolin; Liu, Xin; Mao, Yifei; Xiang, Hong (Journal of Financial Economics, 2025)
Identifying firms’ bond-market-specific economic links through credit-rating comovement of their corporate bonds, a long-short strategy for stocks based on these links generates a risk-adjusted alpha of 0.45% per month, which cannot be explained by existing economic links in the literature. Market segmentation between the equity and bond markets appears to be the underlying mechanism: (i) The cross-return predictability is muted in the bond market; (ii) The cross-return predictability is mitigated in the presence of cross-holding investors; (iii) Equity analysts slowly incorporate information from rating-comovement links to their forecasts.